Respuesta :

This should be the process. 

Please try to understand the steps instead of just writing down the answer, it'll help you a lot.

Ver imagen jijishero
   [tex]2 \sqrt{3} ( \sqrt{6} + 2 \sqrt{5}) [/tex]

   //Distribute the 2√3 over to the two terms in the bracket:
[tex]=( 2)( \sqrt{3})(\sqrt{6}) + (2)( \sqrt{3} )(2)(\sqrt{5}) [/tex]

   //Combine each term
[tex]=2\sqrt{18} + 4\sqrt{15} [/tex]

    //Simplify  square root of 18
[tex]= 2 \sqrt{9 \times 2} + 4 \sqrt{15} } [/tex]

   // Simplest form
[tex]= 6 \sqrt{2} + 4 \sqrt{15} } [/tex]